2019
DOI: 10.12998/wjcc.v7.i17.2450
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of portal vein thrombosis after splenectomy and its influence on transjugular intrahepatic portosystemic shunt stent patency

Abstract: BACKGROUNDTransjugular intrahepatic portosystemic shunt (TIPS) is widely accepted as an alternative to surgery for management of complications of portal hypertension. TIPS has been used to treat portal vein thrombosis (PVT) in many centers since the 1990s. Although TIPS has good therapeutic effects on the formation of PVT, the effect of PVT on TIPS stenting has rarely been reported. Patients with splenectomy and pericardial devascu-larization have a high incidence of PVT, which can markedly affect TIPS stent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…PVT, a complication with a high incidence after splenectomy, is difficult to predict and can affect patient prognosis [ 23 ]. In this study, the overall incidence of PVT was 27.6%, which was close to that found in the reference literature [ 11 , 24 ]. Our study demonstrated that DSV, DPV, BMI, and platelet count may be related to the formation of PVT after splenectomy, which is consistent with previous research results [ 23 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…PVT, a complication with a high incidence after splenectomy, is difficult to predict and can affect patient prognosis [ 23 ]. In this study, the overall incidence of PVT was 27.6%, which was close to that found in the reference literature [ 11 , 24 ]. Our study demonstrated that DSV, DPV, BMI, and platelet count may be related to the formation of PVT after splenectomy, which is consistent with previous research results [ 23 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Qi et al found that patients who underwent splenectomy had a significantly higher rate of shunt dysfunction after TIPS placement (22,23). Furthermore, Yang et al and Dong et al reported that patients with splenectomy had a high incidence of portal vein thrombosis, which can markedly affect TIPS stent patency (14,24). These results are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Treatment with HFC in this paediatric population showed a favourable safety profile; of the 10 AEs reported in this study, only two were assessed as possibly related to HFC; pyrexia and a case of PVT, which was classified as an SAE and led to discontinuation of the patient from the study. PVT is a regular complication of splenectomy, and other studies with and without HFC treatment have also reported thromboembolic events 11,17,24,25 . Patients with CFD have been documented to experience thromboembolic events in the absence of treatment with HFC 25 .…”
Section: Discussionmentioning
confidence: 99%
“…PVT is a regular complication of splenectomy, and other studies with and without HFC treatment have also reported thromboembolic events. 11,17,24,25 PK parameters were determined from the actual values for fibrinogen activity measured pre-and post-infusion. Comparable data were also obtained for PK parameters determined by fibrinogen antigen for the full PK population (data not shown).…”
Section: Discussionmentioning
confidence: 99%